2020
DOI: 10.3390/life10070104
|View full text |Cite
|
Sign up to set email alerts
|

Endosperm of Angiosperms and Genomic Imprinting

Abstract: Modern ideas about the role of epigenetic systems in the regulation of gene expression allow us to understand the mechanisms of vital activities in plants, such as genomic imprinting. It is important that genomic imprinting is known first and foremost for the endosperm, which not only provides an embryo with necessary nutrients, but also plays a special biological role in the formation of seeds and fruits. Available data on genomic imprinting in the endosperm have been obtained only for the triploid en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 94 publications
2
14
0
Order By: Relevance
“…Ploidy levels of endosperm and the presence of maternally derived resource storage tissues, the nucellus or perisperm, are also indicated exist for molecular complexes or pathways rather than individual genes. Difficulties in comparing the distinct modes of endosperm development amongst angiosperms also hinders establishing the degree of conservation (Kordyum and Mosyakin 2020). Regardless of their imprinted status, many imprinted genes have not been connected to obvious phenotypes when knocked out or when their imprinting is removed (Berger et al 2012;Waters et al 2013).…”
Section: Imprinting In Land Plants: a Spotlight On Angiospermsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ploidy levels of endosperm and the presence of maternally derived resource storage tissues, the nucellus or perisperm, are also indicated exist for molecular complexes or pathways rather than individual genes. Difficulties in comparing the distinct modes of endosperm development amongst angiosperms also hinders establishing the degree of conservation (Kordyum and Mosyakin 2020). Regardless of their imprinted status, many imprinted genes have not been connected to obvious phenotypes when knocked out or when their imprinting is removed (Berger et al 2012;Waters et al 2013).…”
Section: Imprinting In Land Plants: a Spotlight On Angiospermsmentioning
confidence: 99%
“…The tight association of imprinting with endosperm in monocots and eudicots raises the question of whether imprinting in land plants is dependent on the existence of endosperm, and if so, whether there is a dependence on triploidy in endosperm. This last point is already questioned by the fact that endosperm ploidy is distinct from the triploid ratio of one paternal to two maternal genomes in some species of monocots and eudicots (Kordyum and Mosyakin 2020 ). Imprinting has not been investigated in land plants outside of monocots and eudicots, but endosperm can be found in ANA-grade angiosperms (Fig.…”
Section: Getting To the Origins Of Imprinting And Endosperm: Ana-grade Angiospermsmentioning
confidence: 99%
“…The greater importance attached to the duplicated maternal genome in the triploid endosperm could have contributed to a more efficient allocation of resources in the embryo sac, since it reduced the influence of competition for maternal resources unrelated among paternal genomes of endosperm [73]. At the same time the actual ploidy of the endosperm nuclei can vary widely depending on the type of embryo sac, the involvement or depression of the lower polar nucleus, the stage of endosperm development and other events [32,[74][75][76][77][78][79][80].…”
Section: Endospermmentioning
confidence: 99%
“…The differences between three types of endosperm -nuclear, cellular and helobialare mainly observed in order variations of mitosis and cytokinesis at the initial stages of endosperm development [51,58,61,[74][75][76][77][78][79][80]. Subsequent stages of endosperm development, such as synthesis and accumulation of reserve nutrients, its presence in mature seeds or its resorption by an embryo do not show any direct connection with its types.…”
Section: Endospermmentioning
confidence: 99%
“…Although other studies have also demonstrated tissue-specific relationships between various chromatin modulators and gene expression [ 57 , 58 , 59 , 60 ], this topic is still a subject of debate. Specialised tissues, such as embryo, endosperm, and pollen, have shown large-scale changes in the expression of specific genes and DNA methylation patterns during Arabidopsis development [ 61 , 62 ]. In pollen and somatic cells, the methylation is maintained by comparable mechanisms; however, higher efficiency of CG methylation maintenance has been noted in pollen, which could contribute to the inheritance of methylation across generations [ 61 ].…”
Section: From Epigenetics To Crop Improvement: Lessons From Arabidopsis and Other Model Plant Speciesmentioning
confidence: 99%